Impact of COVID-19 on Elective Cleft Surgery in Low- and Middle-income Countries - Vander Burg, Richard (Plast Reconstr Surg Glob Open, 2021)
BACKGROUND: The COVID-19 pandemic disrupted health systems worldwide, including in low- and middle-income countries (LMICs). Many countries limited the delivery of elective surgery. To date, COVID-19’s impact on elective surgery in LMICs has been unquantified. We use operative data from a large international non-government cleft organization to compare case volume for 2019 and 2020 to quantify the impact of COVID-19. METHODS: Smile Train supports a partner network of over 1100 partners globally to deliver treatment to children with cleft lip and cleft palate (CLP). Treatment data is documented into a proprietary digital platform, Smile Train Express. We compared monthly treatment data for 2019 to 2020, by country, and by World Bank Income group to describe the effect that the COVID-19 pandemic has had on CLP surgery in LMICs. RESULTS: Our analysis shows 25,444 (31.4%) fewer primary operations performed between January and December 2020 than in the same period in 2019 with the most significant decline in procedures observed in April 2020. Many countries resumed elective surgery for CLP procedures from May onward and volume approximated that of pre-pandemic baseline by November of 2020. CONCLUSIONS: The emergence of the COVID-19 pandemic had a large impact on health systems and service delivery across the world. We find that this is evident in the delivery of CLP surgery in LMICs. The impact is characterized by a dramatic decrease in surgery rates in April of 2020 with a recovery of surgical volume from July 2020 onwards. The rate of surgical rate recovery is consistent across World Bank Income groups.